Relationship between depression and anxiety levels of pregnant women with smoking and caffeine - Şeker, Fatma Dilek; Aydoğdu, Melike; Annette Akgür, Serap (Journal of Dependence, 2019)
Objective: The aim of this study was to investigate pregnant women depression and anxiety levels relations with smoking and caffeine use.Method: Personal information form, Beck Depression and Anxiety Scale, Fagerstrom Test of Nicotine Dependence were applied to the pregnant women who accepted to participate the study (n=156) by using face-to-face interview technique.Results: There was a statistically significant difference between the smoking status of before and during pregnancy. 21,8% of the pregnant women husband smoked beside their wife and 21,8% of the pregnant women were exposed to cigarette smoke in the workplace. Smoking behavior rate was found 8,2% in non-depressive group, 14,7% in mild depressive group and 16,7% in serious depressive group. When the relation between amounts of caffeine consumed before pregnancy and during pregnancy and the age, there was a statistically significant difference in the amount of caffeine consumption before pregnancy between age groups.Conclusion: In Izmir, it was observed that who want to be mother had awareness about smoking and caffeine use during pregnancy. In addition to the verbal explanation of the pregnant women, the best result may be achieved by toxicological screening.
Keywords: Pregnancy; smoking; caffeine; depression; anxiety